2021
DOI: 10.1016/j.jcot.2021.01.006
|View full text |Cite|
|
Sign up to set email alerts
|

The relationship of anterior cruciate ligament injuries with MRI based calculation of femoral notch width, notch width index, notch shape - A randomized control study

Abstract: Background: ACL injuries are infamously known for disability in young adults and require surgical reconstruction. The need of time is to predict predisposing factors and prevent ACL injuries.The incidence of ACL injuries has been associated with various factors related to the morphology of distal femur and proximal tibia.Hence, purpose of this study was to assess the relationship of morphology of distal femur by assessing Notch Width(NW), Notch Width Index (NWI), and Notch shape calculated preoperatively on MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 24 publications
0
11
1
Order By: Relevance
“…Also, there have been radiological as well as anthropometric studies on the Indian population that have noted similar findings [ 8 , 14 ]. Fahim et al noted a notch width of 19.9 mm ± 1.7 mm in the case group and 21.1 mm ± 1.9 mm in the control group; a NWI of 0.27 ± 0.01 in the case group; and 0.31 ± 0.01 in the control group [ 8 ]. Similarly, Park et al noted that the mean value of notch width measured 17.37 mm in the ACL-injured patients, and 20.33 mm in the control population, with an NWI of 0.23 ± 0.01 in the case group and 0.24 ± 0.01 in the control group [ 7 ].…”
Section: Discussionmentioning
confidence: 68%
“…Also, there have been radiological as well as anthropometric studies on the Indian population that have noted similar findings [ 8 , 14 ]. Fahim et al noted a notch width of 19.9 mm ± 1.7 mm in the case group and 21.1 mm ± 1.9 mm in the control group; a NWI of 0.27 ± 0.01 in the case group; and 0.31 ± 0.01 in the control group [ 8 ]. Similarly, Park et al noted that the mean value of notch width measured 17.37 mm in the ACL-injured patients, and 20.33 mm in the control population, with an NWI of 0.23 ± 0.01 in the case group and 0.24 ± 0.01 in the control group [ 7 ].…”
Section: Discussionmentioning
confidence: 68%
“…11 As anatomical factors, the intercondylar notch width and PTS have been extensively investigated as risk factors for noncontact ACL injuries. 5,9,19,21,25,27 Type A intercondylar notch, which is narrow from the base to the midsection as well as at the apex, was associated with a significantly increased probability of suffering a noncontact ACL injury in female (OR, 4.99) and male (OR, 5.50) patients. 1 An increased alpha angle between the long axis of the distal femur and the Blumensaat line was the most significant factor associated with an ACL injury.…”
Section: Discussionmentioning
confidence: 99%
“…S.M. Fahim et all in their randomised control study used MRI for the calculation for NWI, reported that there were no differences in NWI in either sex and the NWI was significantly lower in those with ACL injury [28]. Ashwini et al, in their MRI based comparative study, demonstrated that people with ACL injury had NWI of 0.29 ± 0.02 or lesser compared to those without an ACL injury, whereas Bhasukala et al, postulated the cutoff of NWI to be 0.28 ± 0.06.21.…”
Section: Notch Parametersmentioning
confidence: 99%